1999
DOI: 10.1001/archderm.135.12.1467
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Diagnosis vs Telediagnosis of Pigmented Skin Tumors

Abstract: Background: Teledermoscopy uses telecommunication technologies to transfer images of pigmented skin lesions, including clinical and anamnestic data, via email to specialized centers for teleconsultation.Design: Sixty-six pigmented skin lesions examined on a face-to-face basis in a skin lesion clinic in L'Aquila, Italy, were sent via e-mail on a standard-resolution color monitor for consultation at a university dermatology department in Graz, Austria.Intervention: Digital photographs of the clinical and dermosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 37 publications
3
112
1
5
Order By: Relevance
“…Most of these studies demonstrate high accordance for the diagnosis of inflammatory and neoplastic skin diseases [17, 18, 19, 20, 21], and particularly for the diagnosis of pigmented skin lesions (teledermoscopy) [22, 23, 24, 25, 26]. Up to now only a few reports have discussed the use of teledermatology in the diagnosis and care of patients with leg ulcers [27, 28, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies demonstrate high accordance for the diagnosis of inflammatory and neoplastic skin diseases [17, 18, 19, 20, 21], and particularly for the diagnosis of pigmented skin lesions (teledermoscopy) [22, 23, 24, 25, 26]. Up to now only a few reports have discussed the use of teledermatology in the diagnosis and care of patients with leg ulcers [27, 28, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Similar values could be provided by computer-based expert systems using digital dermoscopy [Schindewolf et al, 1994;Horsch et al, 1997;Binder et al, 1998;Menzies, 1999;Pompl et al, 1999;Seidenari et al, 1999]. Digital images bear also the possibility of teledermoscopy by connecting private dermatological practices with specialists at a dermoscopy center [Glaessl et al, 1999;Piccolo et al, 1999;Glaessl et al, 2000;Argenziano et al, 2000;Braun et al, 2000]. For regular monitoring of melanocytic nevi, simultaneous comparison of images is inevitable and digital dermoscopy appears to be most practicable [Stolz et al, 1996;Kittler et al, 1999;Kittler et al, 2000;Menzies et al, 2001].…”
Section: Patientenvertrauen In Dermatoskopische Methoden Zur Entdeckumentioning
confidence: 94%
“…It has previously been demonstrated [1] that open-access teledermatology may serve as a successful platform [9,10] for challenging dermoscopic cases, where advice on diagnosis and therapy can be provided. This is emphasized by the fact that past studies have shown a high diagnostic concordance between telediagnosis and face-toface diagnosis for pigmented lesions [11][12][13] . The possibility of searching for a combination of dermoscopic and clinical features in the case archive is, to the best of our knowledge, unique and allows the image archive to serve as a form of encyclopaedia.…”
Section: Discussionmentioning
confidence: 99%